Lessons from isavuconazole therapeutic drug monitoring at a United Kingdom Reference Center. (12th May 2020) - Borman, Andrew M; Hughes, Jessica M; Oliver, Debra; Fraser, Mark; Sunderland, Julie; Noel, Alan R; Johnson, Elizabeth M
Abstract: We determined isavuconazole serum concentrations for 150 UK patients receiving standard isavuconazole dosing regimens, including serial therapeutic drug monitoring for several patients on prolonged therapy. Mean trough isavuconazole concentrations in these patients were virtually identical to those reported previously from clinical trials, although greater variability was seen in patients below 18 years of age. Serial monitoring in patients receiving prolonged therapy suggested gradual, near-linear accumulation of the drug over many weeks.